2009
DOI: 10.2174/157488409787236119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy and Safety of Fixed Dose Combination of Ceftazidime-Tobramycin in Comparison with Ceftazidime in Lower Respiratory Tract Infections

Abstract: Lower respiratory tract infections are major cause of morbidity and mortality. Objectives were to evaluate efficacy and safety of fixed dose combination (FDC) of Ceftazidime and Tobramycin in comparison with Ceftazidime alone in patients with lower respiratory tract infections. Patients (n=240) were randomly distributed in two arms: one arm was treated with Ceftazidime(1g)-Tobramycin(120mg) and other arm was treated with Ceftazidime (1g) alone. Patients were clinically, radiologically and bacteriologically eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…1). The trials were divided into six major clinical categories based on the type of infection addressed (Table 1): febrile neutropenia (21 trials [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]); pneumonia, including one trial with lower respiratory tract infection (8 trials [91][92][93][94][95][96][97][98]); abdominal or urinary tract infection (4 trials [99][100][101][102]); severe sepsis or bacteraemia (10 trials [73,[103][104][105][106][107][108][109][110][111]); endocarditis (4 trials [112][113][114][115]); and CF or bronchitis (8 trials [116][117]…”
Section: Resultsmentioning
confidence: 99%
“…1). The trials were divided into six major clinical categories based on the type of infection addressed (Table 1): febrile neutropenia (21 trials [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]); pneumonia, including one trial with lower respiratory tract infection (8 trials [91][92][93][94][95][96][97][98]); abdominal or urinary tract infection (4 trials [99][100][101][102]); severe sepsis or bacteraemia (10 trials [73,[103][104][105][106][107][108][109][110][111]); endocarditis (4 trials [112][113][114][115]); and CF or bronchitis (8 trials [116][117]…”
Section: Resultsmentioning
confidence: 99%
“…Four of the eight RCTs evaluating antibiotics found no difference in clinical efficacy when comparing the following antibiotic regimens: gatifloxacin vs ceftriaxone (92% and 88% cure rate; P -value not reported), biapenem vs meropenem (94.7% vs 93.75% clinical efficacy; P -value not reported), levofloxacin five day vs seven day course (cure rate 56% vs 56.8%; difference = -0.8; 95% CI = -13.9 to 12.3) and levofloxacin vs ceftriaxone with azithromycin (hospital LOS 3.3 vs 3.4; P = 0.15) [ 59 , 61 , 63 , 64 ]. Abengowe et al [ 57 ] found higher cure rates (68.2% vs 36.5%; P < 0.01) with TMP-SMX over tetracycline in Nigeria, and Chaudhary et al [ 58 ] found benefit for ceftazidime-tobramycin over ceftriaxone in India (88.4% vs 61.2%; P -value not reported), although with high risk of bias. Tieying et al [ 62 ] found that clinical cure at seven days was greater for moxifloxacin over levofloxacin/metronidazole (76.7% vs 51.7%; P = 0.045) among patients with CAP with aspiration risk factors at seven days, although no difference at the end of the treatment period at 14 days (83.3% vs 71.8%; P = 0.233).…”
Section: Resultsmentioning
confidence: 99%
“…Tobracef, is one such novel drug (under patent protection) which is a combination of third-generation beta lactam antibiotic ceftazidime and tobramycin in a ratio of 8.33:1, supplied with solvent. Tobracef has been demonstrated to have noticeable antibacterial activity [24]. Its antibacterial activity has also been proved in animal model [25].…”
Section: Introductionmentioning
confidence: 99%